2018
DOI: 10.1080/02607476.2017.1415514
|View full text |Cite
|
Sign up to set email alerts
|

‘I love a curry’: student-teacher discourse around ‘race’ and ethnicity at a UK university

Abstract: This paper presents aspects of a small-scale study that considered student teachers' language and discourse around race and ethnicity at a university in the northwest of England. The first part of the paper critiques current education-related policy, context and practice to situate the research and then draws upon aspects of critical race theory and whiteness theory as frames of reference. In the research, 250 student-teachers completed questionnaires that invited responses to statements about race and ethnici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Cardona Molto et al, (8) broadly differentiated the responses of the university students from Spain, England and the United States into relativist and ethnocentric views and stated that students with a relativist point of view have a more positive attitude towards diversity and differences than ethnocentric students. These differences and diversity as revealed by Dunne et al, (9) have induced a sense of discomfort among trainee teachers. They hesitate in revealing their feelings about the situation as talking about differences on the basis of race and ethnicity will offend others.…”
Section: Complexity Of Identitiesmentioning
confidence: 96%
See 2 more Smart Citations
“…Cardona Molto et al, (8) broadly differentiated the responses of the university students from Spain, England and the United States into relativist and ethnocentric views and stated that students with a relativist point of view have a more positive attitude towards diversity and differences than ethnocentric students. These differences and diversity as revealed by Dunne et al, (9) have induced a sense of discomfort among trainee teachers. They hesitate in revealing their feelings about the situation as talking about differences on the basis of race and ethnicity will offend others.…”
Section: Complexity Of Identitiesmentioning
confidence: 96%
“…All of the studies included for literature synthesis revealed that issues related with diversity are high on policy priority, and measures in attitude change have become tool for change [6,[8][9][10]. As a way of working with diversity, teacher educators from Norway suggested to actively draw attention on the prior experiences and background of the students, to start working on diversity within the classroom of ATs [6].…”
Section: Dealing With Diversity Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Schools are no longer legally required to report and monitor racist incidents as they were following the Race Relations Amendment Act 2000, but instead, have a duty to promote "fundamental British values" (Department for Education, 2014b) and, under the Prevent duty (Department for Education, 2015), to monitor and report any pupils deemed to be at risk of radicalization. Dunne et al (2018) argue that this shift contributes to a silencing of more critical discussion relating to race equality, fuelled by a misplaced notion that "race has been 'dealt with' in a post-racial era" (p. 163). Other critiques of the focus on fundamental British values (e.g., Farrell, 2016;Smith, 2016) have concluded that this not only serves to silence or marginalize racism as a concern, but could be interpreted as a more dangerous apparatus through which inequality and injustice remain beyond scrutiny, and the concept of a nationalistic cultural homogeneity is promoted.…”
Section: Teacher Education "Race" and Whitenessmentioning
confidence: 99%
“…It should be pointed out that the duty to promote fundamental British values was not statutory at the time when the data upon which this paper draws was collected. It is however, important to acknowledge such change as it serves as evidence that the political context within which ITE is delivered has become more complex, and the critical spaces within educational discourse and policy have subsequently become even more eroded (Dunne et al, 2018;Warmington et al, 2018).…”
Section: Teacher Education "Race" and Whitenessmentioning
confidence: 99%